2020
DOI: 10.1016/j.jsxm.2020.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Penile Size Dissatisfaction

Abstract: Background: Men concerned about their penis size often consult professionals working in urology, andrology, surgery, and sexual medicine. Aim: To inform professionals in the sexual medicine field about small penis syndrome as a clinical syndrome and to provide recommendations for treatment. Methods: This was an overview of the existing literature combined with our extensive clinical experience. Results: Small penis syndrome is a syndrome with psychiatric comorbidities and social consequences that impair life. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Surgery on men with penises longer than this is viewed by many professionals as cosmetic and unnecessary, with serious ethical issues (Dillon et al, 2008;Mondaini et al, 2002;Vardi, 2006;Wylie & Eardley, 2007), yet penile enlargement surgeries for cosmetic purposes are increasing (Littara, Melone, Morales-Medina, Iannitti, & Palmieri, 2019;Wylie & Eardley, 2007). Instead of surgery, psychological counseling and sex education should be offered, with particular emphasis on educating men about the normal range of values for penis size (Dillon et al, 2008;Mondaini et al, 2002;Pastoor & Gregory, 2020;Wylie & Eardley, 2007). A recent review of many studies has found that counseling is often effective in convincing a majority of men who worry about having a small penis that their penis is of normal size (Marra et al, 2020).…”
Section: Implications For Counseling and Surgical Interventionmentioning
confidence: 99%
“…Surgery on men with penises longer than this is viewed by many professionals as cosmetic and unnecessary, with serious ethical issues (Dillon et al, 2008;Mondaini et al, 2002;Vardi, 2006;Wylie & Eardley, 2007), yet penile enlargement surgeries for cosmetic purposes are increasing (Littara, Melone, Morales-Medina, Iannitti, & Palmieri, 2019;Wylie & Eardley, 2007). Instead of surgery, psychological counseling and sex education should be offered, with particular emphasis on educating men about the normal range of values for penis size (Dillon et al, 2008;Mondaini et al, 2002;Pastoor & Gregory, 2020;Wylie & Eardley, 2007). A recent review of many studies has found that counseling is often effective in convincing a majority of men who worry about having a small penis that their penis is of normal size (Marra et al, 2020).…”
Section: Implications For Counseling and Surgical Interventionmentioning
confidence: 99%
“…SPA, also known as "small penis syndrome," a type of BDD, is characterized by anxiety related to one's genitals, either directly or indirectly (while clothed), stemming from concerns about the size of the flaccid penis, despite clinical evidence suggesting otherwise [ 7 ]. Men who are distressed about the size of their penis often seek consultations with professionals in urology, andrology, surgery, dermatology, psychiatry, and sexual medicine [ 8 , 9 ]. The syndrome can lead to feelings of inadequacy causing significant distress, anxiety, and depression along with negative work-related and social implications [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Men who are distressed about the size of their penis often seek consultations with professionals in urology, andrology, surgery, dermatology, psychiatry, and sexual medicine [ 8 , 9 ]. The syndrome can lead to feelings of inadequacy causing significant distress, anxiety, and depression along with negative work-related and social implications [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…22,27,31,32 The epidemiology of this condition is not known. 33 Few theories are proposed regarding this condition such as impaired neurological development (tactile stimulation and perineal sensation), dysfunction in the parietal lobe (association areas), and other contributing factors (cognition and disgust effect also cognition of parts belonging to self). 10 Normal penile measurement and adequate sexual and voiding function were found in 98% of men who were concerned about their penile size.…”
Section: Small Penis Anxiety (Spa) and Penile Dysmorphophobia Disorde...mentioning
confidence: 99%